Transitions of Care: Improving the Quality of Discharge Summaries Completed By Internal Medicine Residents - Meghan Black; Cristin M. Colford (Association of American Medical Colleges, 2017)
Introduction Discharge summaries are now the accepted means of communication in transition from inpatient to ambulatory care. However, there is often no formal residency education on this critical document, leading to discordance in discharge summaries written by internal medicine residents. There is little in the literature focusing on teaching how to effectively create a discharge summary using an electronic health record (EHR). Methods A 1-hour workshop was designed to teach components of the discharge summary and how to utilize this document to safely transition patients from the inpatient to the ambulatory setting. One or two faculty facilitators led the workshop with approximately 20 resident learners. A 50-point rubric was created to assess effectiveness of discharge summaries pre- and postworkshop. Results The workshop was well received by residents and median scores on the rubric improved from 39 to 45 (p < .001) postworkshop. Discussion We found that by teaching the concepts using examples of discharge summaries written by our residents, and then creating a standardized EHR template, residents wrote more effective discharge summaries with increased focus on the transition to the ambulatory provider. These materials can be applied to other programs and levels of learners to improve discharge summary quality. This serves to provide a resource to those at other institutions looking to create a more formalized didactic session on discharge summaries with a particular focus on transitioning care to the ambulatory provider.